Mature dengue virus particles inactivated by a non-ionic detergent retain quaternary neutralizing epitopes and induce potent neutralizing antibodies - Tsai, Wen-Yang; Pierson, Theodore C.; Wrammert, Jens; Dejnirattisai, Wanwisa; Jumnainsong, Amonrat; Mongkolsapaya, Juthathip; Screaton, Gavin; Crowe, James E.; Wang, Wei-Kung (Frontiers in Immunology, 2025)
IntroductionThe four serotypes of dengue virus (DENV1-4) are the leading cause of arboviral diseases in humans. Currently, developing a safe and effective DENV vaccine remains a challenge. Previously we reported potently neutralizing human monoclonal antibodies (mAbs) preferentially recognize mature DENV particles, on which there is limited access to the fusion loop (FL) epitope and no premembrane (prM) protein. As FL and prM antibodies are weakly- or non-neutralizing and contribute to antibody-dependent enhancement, mature DENV particles represent an ideal DENV vaccine candidate. Several inactivated flavivirus vaccines, generated using formalin, ultraviolet or other inactivation methods, have progressed through preclinical and clinical studies. Little is known about how different inactivation methods affect viral epitopes and the quality of antibodies induced.MethodsWe investigated epitopes on Tween 20-inactivated mature DENV1 particles by testing a panel of well-characterized human mAbs and membrane integrity by sucrose-gradient ultracentrifugation and protein K digestion. We examined the mechanisms of Tween 20 inactivation by measuring RNA copy numbers, virus binding to cells and acid exposure, and antibody responses induced by Tween 20-inactivated mature DENV1 particles in mice.ResultsTween 20 inactivation better preserved the epitopes recognized by potently neutralizing mAbs compared with other methods. Sucrose-gradient ultracentrifugation and protein K digestion revealed no disruption of membrane integrity by Tween 20. Mechanistically, Tween 20 treatment caused reduced virus binding to cells and RNA degradation, which was reverted by pre-treatment with RNAseOUT, suggesting the involvement of extracellular RNase, and prevented the envelope protein conformational changes induced by acid exposure. Moreover, Tween 20-inactivated mature DENV1 particles induced a neutralizing antibody response to all four DENV serotypes characterized by competition with several potently neutralizing mAbs and limited recognition of FL.ConclusionOur results suggest that Tween 20-inactivated mature particles are a promising strategy for DENV vaccine development.